2019
DOI: 10.1007/s11136-019-02356-w
|View full text |Cite
|
Sign up to set email alerts
|

Factorial structure of the Manchester Short Assessment of Quality of Life in patients with schizophrenia-spectrum disorders

Abstract: Purpose Subjective quality of life is a central patient-reported outcome in schizophrenia-spectrum disorders. The Manchester Short Assessment of Quality of Life (MANSA) is an established and widely used instrument for its assessment. The present study is a secondary analysis of large schizophrenia studies and aims to establish the factorial structure of the MANSA with a rigorous two-step methodology. Methods A sample of 3120 patients was randomly split into two datasets; the first includes two thirds of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Higher scores indicate better QoL. MANSA has sound psychometric properties and is widely used [ 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate better QoL. MANSA has sound psychometric properties and is widely used [ 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores thus indicate better quality of life. A recent study concluded that the items form two factors [ 40 ]. One concerns “life and health-related aspects”, encompassing items pertaining to life as a whole, mental health, physical, leisure activities, friendships, employment situation, financial situation, and sex life.…”
Section: Methodsmentioning
confidence: 99%
“…Also, participants reported satisfaction with the quality and quantity of friendships, measured using the sixteen items of the Manchester Short Assessment of Quality of Life (MANSA), which was rated on a score from 1 (very dissatisfied) to 7 (very satisfied). MANSA is a reliable measure and has been used to assess the quality of life of people with mental health conditions (5,27,28). Two direct COVID-19-related questions were asked to participants to know how the coronavirus pandemic affected the amount of contact they have with people outside of their homes.…”
Section: Survey Procedures and Measuresmentioning
confidence: 99%